Penyuluhan Kesehatan Tentang Pencegahan Penyakit Tuberkulosis Paru kepada Warga Binaan Pemasyarakatan di Lapas Klas II Padangsidimpuan Tahun 2019 - Ramadhini, Delfi; Yunizar, Aida (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2020)
Pulmonary tuberculosis is a chronic infectious disease that has become a global issue. In Indonesia, this disease is one of the national priorities for disease control programs because it has a wide impact on the quality of life and economy and causes death. The World Health Organization (WHO) estimates the prevalence of TB disease in the world, with 582,000 new cases per year, nearly half of which are smear positive pulmonary tuberculosis. The purpose of this PKM is to motivate the prisoners in class II prisons about the importance of preventing pulmonary tuberculosis. PKM activities are carried out by means of health education methods using a powerpoint slide show media to the Correctional Assistance Citizens at the Class II Padangsidimpuan Prison. The results of this outreach activity were continued by providing an evaluation to the Correctional Assistance Citizens in Class II Lapas, namely questions and answers about the material given. There are three questions given by the extension agent to the Correctional Assistance Citizens in Class II Lapas. Based on the answers given, it shows that the Correctional Assistance in Class II Lapas understands the material provided by the extension agent. PKM activities carried out went well. Residents of the Correctional Assistance at the Padangsidimpuan Class II Lapas who participated in the activity seemed enthusiastic about participating in the counseling activities.